2014
DOI: 10.1111/apa.12745
|View full text |Cite
|
Sign up to set email alerts
|

Impaired balance and neurodevelopmental disabilities among children with congenital cytomegalovirus infection

Abstract: Congenital CMV infection affects the general development of the brain and gives rise to a complex pattern of difficulties. Identifying comorbid conditions is very important, as children with associated difficulties and disabilities need more support than children with just hearing impairment. Congenital CMV infection needs to be considered in children with hearing impairment and/or balance disturbance and/or neurodevelopmental disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 23 publications
7
74
2
3
Order By: Relevance
“…Karltorp et al [2014] observed a higher association with cognitive impairment in children with CMV-induced HL than in those with HL caused by GJB2 mutations. Thus, systematic CMVpi screening may improve their management, and a long-term follow-up of a large cohort of newborns with CMVpi would provide better understanding of the impact on cognitive development.…”
Section: Discussionmentioning
confidence: 73%
“…Karltorp et al [2014] observed a higher association with cognitive impairment in children with CMV-induced HL than in those with HL caused by GJB2 mutations. Thus, systematic CMVpi screening may improve their management, and a long-term follow-up of a large cohort of newborns with CMVpi would provide better understanding of the impact on cognitive development.…”
Section: Discussionmentioning
confidence: 73%
“…Milewska-Bobula et al 29 indicated increased emotional sensitivity and problems with school maturity in 6-year-old children with asymptomatic or mildly symptomatic cCMV infection, and Karltorp et al 30 showed that 88% of 26 children with congenital CMV infection had balance disturbances including walking at a later age. Whether WMAs in cCMV infection cause a subsequent developmental disorder is still unclear,14 25 26 and newborns and infants with SNHL in our study showed far more abnormal CNS findings other than WMAs than those without SNHL; thus SNHL could occur in children with more severely damaged CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The critical appraisal of the 30 studies is presented in Table . One study was a prospective cohort study, all other studies were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study was a prospective cohort study, all other studies were retrospective studies. Twenty‐three studies included children with cCMV‐related hearing loss as well as children with other causes of hearing loss . Eleven studies directly compared a cCMV‐group to a non‐cCMV‐group .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation